A multi-hop and multi-path store and forward system, method and product for bulk transfers - (:unkn) unknown (My University, 2012)
A multi-hop and multi-path store and forward system for bulk transfers comprising a plurality of nodes (100) wherein each node (100) also comprises an overlay management module (1) that is arranged to add a new node (100) to the overlay, removing it, and maintaining the overlay connections during the node's participation in the system; a volume prediction module (2) which is arranged to maintain a time series with the predicted maximum volume of data that can be forward to each neighbour node during each one of the slots that make an entire day; bootstrapping, ISP - friendliness, and security means; a scheduling and routing module (3) for all data transfers between a sender v, storage nodes w and a receiver node u; and wherein the module (3) also comprises volume prediction means to calculate an initial transfer plan and keeps updating it periodically as it receives updated predictions from the nodes, and means for solving a maximum network flow optimization problem; and wherein a transmission management module (4) is arranged to receive, scheduling and routing commands from the scheduling and routing module (3) of senders v for which a local node is forwarding and executes them accordingly. Aim of the system is to split a large file into multiple chunks using a number of intermediate storage nodes to bypass MTABs (Multiple Time aligned Bottlenecks) and shorten the delivery times for bulk data.
Keywords: International Classification H04L29/06; Multi-hop store; Multi-path store; International Classification H04L29/06 Cooperative Classification H04L67/325, H04L67/06, H04L45/24; European Classification H04L29/08N5, H04L29/08N31T, H04L45/24